Directives for the conservation of the northern muriqui, Brachyteles hypoxanthus (Primates, Atelidae) - Mendes, Sérgio L.; Melo, Fabiano R.; Boubli, Jean P.; Dias, Luiz G.; Strier, Karen B.; Pinto, Luiz Paulo S.; Fagundes, Valeria; Cosenza, Braz; Marco Jr, Paulo (Neotropical Primates, 2005)
There are two species of muriqui, Brachyteles — the northern muriqui (B. hypoxanthus) and the southern muriqui (B. arachnoides). The northern muriqui is the most endangered of the two. The species originally occurred through most of the Atlantic forest in the south of the state of Bahia, eastern Minas Gerais, and south central Espírito Santo. Hunting and widespread loss of its native forest means that today just a few small and isolated populations remain, with poor chances of survival in the long term. Currently the northern muriqui can be found in 12 places, six on private land, three in state protected, and three in federal protected areas. Combined, these areas total about 160,000 ha and a minimum known number of 855 individuals. The known population has increased significantly in the last five years, but the total is still very small and fragmented for long-term viability — no single population exceeds 500. In this article we report on the areas where they are known to occur, the main threats to them, and the conservation measures that have been proposed to avoid the premature extinction of the species.